Using Real-Time PCR to Investigate Some of Antibiotic Resistance Genes from Streptococcus agalactiae Isolates from ewe Mastitis cases in Nineveh province - Ayman Mohamed Jaber Albanna; Aseel A. H. Al-Layla (مجلة بغداد للعلوم)
In this study, from a total of 856 mastitis cases in lactating ewes, only 34 Streptococcus agalactiae isolates showed various types of resistance to three types of antibiotics (Penicillin, Erythromycin and Tetracycline). St. agalactiae isolates were identified according to the standard methods, including a new suggested technique called specific Chromogenic agar. It was found that antibiotic bacterial resistance was clearly identified by using MIC-microplate assay (dilution method). Also, by real-time PCR technique, it was determined that there were three antibiotics genes resistance ( pbp2b, tetO and mefA ). The high percentage of isolate carried of a single gene which was the Tetracycline (20.59%) followed by percentage Penicillin was (17.65%) and the lowest was in Erythromycin (11.77%). However, there were many isolates that carried two genes of antibiotics resistance represented by Penicillin and Erythromycin with collective present of 38.22%, and for the Penicillin and Tetracycline, the percentage was found to be 11.77%. In contrast, no common gene with two antibiotics (Erythromycin and  Tetracycline) was detected. On the other hand, it was found that no bacterial sharing with three kinds of antibiotic resistance genes ( pbp2b, tetO and mefA ). This study has revealed that the St. agalactiae isolates did induce recurrent mastitis in lactating Iraqi's ewes.